2017
DOI: 10.1371/journal.pone.0185206
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma proline concentrations are associated with sarcopenia in the elderly

Abstract: Background and purposeMetabolome analyses have shown that plasma amino acid profiles reflect various pathological conditions, such as cancer and diabetes mellitus. It remains unclear, however, whether plasma amino acid profiles change in patients with sarcopenia. This study therefore aimed to investigate whether sarcopenia-specific changes occur in plasma amino acid profiles.MethodsA total of 153 community-dwelling and seven institutionalized elderly individuals (56 men, 104 women; mean age, 77.7±7.0 years) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 44 publications
6
47
0
Order By: Relevance
“…These metabolic changes seem to compensate for the reduction in energy production from pyruvic acid in the skeletal muscle. Indeed, the Pro level was significantly elevated in the mice fed the Trp-deficient diet, which concurs with the data describing the serum amino acids associated with sarcopenia in older people [7]. Glucose is the main energy fuel for humans and is stored as glycogen, primarily in the liver and skeletal muscle.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These metabolic changes seem to compensate for the reduction in energy production from pyruvic acid in the skeletal muscle. Indeed, the Pro level was significantly elevated in the mice fed the Trp-deficient diet, which concurs with the data describing the serum amino acids associated with sarcopenia in older people [7]. Glucose is the main energy fuel for humans and is stored as glycogen, primarily in the liver and skeletal muscle.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, metabolomics analysis has been used to understand how amino acid profiles are affected by glucose metabolism [4], aging [5], and cancer [6]. Toyoshima et al [7] have reported an association between plasma amino acid profiles and age-related sarcopenia, and demonstrated that sarcopenia was correlated with lower tryptophan (Trp) and histidine (His) and higher glutamine (Gln) and proline (Pro) concentrations. Furthermore, plasma Trp and His concentrations are often reduced in patients with particular types of cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…2a). Plasma amino acid profiling of patients with sarcopenia—a condition of muscle wasting associated with aging—showed elevated plasma proline levels 29 , indicating that elevated free circulating proline is a common feature of muscle wasting. We identify a proline vulnerability of obesity-enhanced tumours; SLC36-family proline transporter Path is required for tumour growth and exogenous proline promotes tumourigenesis through Path (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14 A total of 25 participants with sarcopenia or cognitive impairments were excluded, because these age-related disorders potentially affect plasma amino acids. [15][16][17] Eight participants with missing data were also excluded. The present study was carried out in accordance with the Declaration of Helsinki, and the study protocol was approved by the ethics committees of the Tokyo Medical and Dental University (#2146) and Ajinomoto (#2015-009).…”
Section: Methodsmentioning
confidence: 99%